Invertebrates are declining in boreal aquatic habitat: the effect of brownification? - Céline Arzel; Petri Nummi; Lauri Arvola; Hannu Pöysä; Aurélie Davranche; Martti Rask; Mikko Olin; Sari Holopainen; Risto Viitala; Eeva Einola; Sanni Manninen-Johansen (Elsevier BV, 2022)
Surface water browning affects boreal lakes in the Northern Hemisphere. This process is expected to increase with global warming. Boreal lakes are the most numerous lakes on Earth. These ecosystems are particularly sensitive to disturbances due to their low biodiversity compared to other aquatic environments. The recent darkening of surface water is expected to hinder key ecosystem processes, particularly through lower primary productivity and loss of biodiversity. However, studies based on long-term data collections have rarely been conducted on the ecological consequences of water browning on aquatic food webs, especially concerning its impacts on invertebrate communities.
For the first time, our analysis based on two decades of data collection in Finnish lakes highlighted a relation between water browning and a decline in aquatic macroinvertebrate abundances. Aquatic invertebrates are the main food resource for many secondary predators such as fish and waterbirds, hence such effect on their populations may have major consequences for boreal ecosystem functioning.